2022
DOI: 10.1037/mac0000011
|View full text |Cite
|
Sign up to set email alerts
|

Reading aloud improves proofreading (but using Sans Forgetica font does not).

Abstract: Proofreading is an important cognitive skill, yet methods for enhancing error detection have received little research attention. We report two experiments comparing the efficacy of proofreading aloud (i.e., "production")-a common proofreading tip-versus in a disfluent font (Sans Forgetica) purported to introduce a desirable difficulty. Participants read eight short texts silently, eight aloud, and eight in the disfluent font-and recorded the noncontextual errors (i.e., typos) and contextual errors (i.e., gramm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Our reasoning could also explain the consistent null results found with reading passages ( [23,30] Experiment 3, [31][32][33])-SF only creates letter-level difficulty, once the word(s) are identified/read, SF does not interfere or support the memory for the ideas those words conveyed. This letter-level difficulty could also be why SF made non-contextual errors (i.e., typos) in passages from Cushing & Bodner [35] more difficult to detect. There may be confusability between similar looking SF-letters that made typos more difficult to detect, but this impairment could also enlighten us on how people read words in SF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our reasoning could also explain the consistent null results found with reading passages ( [23,30] Experiment 3, [31][32][33])-SF only creates letter-level difficulty, once the word(s) are identified/read, SF does not interfere or support the memory for the ideas those words conveyed. This letter-level difficulty could also be why SF made non-contextual errors (i.e., typos) in passages from Cushing & Bodner [35] more difficult to detect. There may be confusability between similar looking SF-letters that made typos more difficult to detect, but this impairment could also enlighten us on how people read words in SF.…”
Section: Discussionmentioning
confidence: 99%
“…Research in this area may benefit from out-of-the-box thinking-not simply asking in which domains SF is beneficial but how SF can be used in those domains. One good example of this is Cushing and Bodner [35] who investigated whether SF can be used to detect errors when proofreading one's written drafts. Given our results of better word recognition when tested in SF, perhaps an application can be using the font to test oneself after one has already studied the material in a fluent font, almost like using SF as a cued recall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies examining how using a perceptually difficult-to-process typeface with an increased desirable difficulty designed specifically to reduce legibility, such as Sans Forgetica, found either no processing or memory benefit of such typefaces or even yielded a memory cost (Geller et al, 2020;Taylor et al, 2020;Wetzler et al, 2021;Cushing and Bodner, 2022;Maxwell et al, 2022). However, there is also a whole series of studies which showed that poorer fluency of the text or desired difficulty in the fluency of the text resulted in better processing of the text and consequently in better memorisation of the read content (Diemand-Yauman et al, 2011;Macdonald and Lavic, 2011;Bjork et al, 2013;Halin, 2016;Pieger et al, 2016).…”
Section: Text Comprehension and Memorisationmentioning
confidence: 99%